Tracking Hermes, pursuing Mercury - Miller, John F.; Clay, Jenny Strauss (Oxford University Press, 2019)
Of all the divinities of classical antiquity, the Greek Hermes (Mercury in his Roman alter ego) is the most versatile and enigmatic. Utilising a multidisciplinary approach, this volume offers an overview of the myriad aspects of this elusive figure, tracking the god's footprints across the many domains in which he partakes.
This edition previously issued in print: 2019. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on February 4, 2019)
Keywords: Hermes -- (Greek deity); Mercury -- (Roman deity); Konferenzschrift -- 2014 -- Virginia; Aufsatzsammlung; Merkur <Gott>; Hermes